La inteligencia artificial en la contratación pública: Marco jurídico para su adquisición y aplicación en los procesos de compra - Vázquez Matilla, Francisco Javier (2025)
This paper addresses artificial intelligence (AI) both as a tool to support contract management and as a direct object of public procurement. From this latter perspective, it examines the legal, technical and operational risks involved in acquiring AI systems, particularly regarding interoperability, data protection and competition. Based on the Spanish and EU regulatory frameworks, the paper identifies key elements for promoting ethical, innovation-friendly procurement. These include preliminary market consultations, project competitions, regulatory sandboxes and results-oriented service level agreements aimed at enhancing competition and facilitating the participation of SMEs and startups.